Inclusion of vitexin in β-cyclodextrin: preparation, characterization and expectorant/antitussive activities. Issue 12 (December 2020) - Costa, Eliatania Clementino; Menezes, Pedro Modesto Nascimento; de Almeida, Ricardo Lúcio; Silva, Fabrício Souza; de Araújo Ribeiro, Luciano Augusto; de Silva, James Almada; de Oliveira, Ana Paula; da Cruz Araújo, Edigênia Cavalcante; Rolim, Larissa Araújo; Nunes, Xirley Pereira
Abstract: The study aimed to include the isolated vitexin of Jatropha mutabilis in the β-cyclodextrin cavity to improve the solubility of this flavone. Its characterization was performed by techniques such as 1 H NMR/ROESY (Nuclear Magnetic Resonance Spectroscopy), FT-IR (Infrared Spectroscopy with Fourier Transform), SEM (Morphological analysis of IC by Scanning Electron Microscopy) and dissolution study in vitro . In addition, the following activities were evaluated in the animal models: expectorant, phenol red dosage in bronchoalveolar lavage and antitussive, cough induced by citric acid. In the characterization of the complex, interaction between hydrogens of ring B of vitexin and (H3) of β-CD was observed, in addition to changes in morphology. In the dissolution test, an increase in the rate of dissolution of vitexin was observed in the first 30 min for the CI vitexin/β-CD when compared with vitexin. Regarding the pharmacological activity, it was observed that the inclusion complex (IC) vitexin/β-CD in the equivalent doses of 0.2, 1 and 5 mg/kg of flavone presented higher expectorant activity when compared to vitexin (p < 0.05), suggesting increased bioavailability. As for the antitussive activity, both vitexin and the complex had similar effects and were dose independent. In the toxicity test using Artemia salina, vitexin and IC vitexin/β-CD were considered non-toxic. At last, the study efficacy of vitexin/β-CD IC as an expectorant and of vitexin as antitussive. All of these data are being described for the first time. Abstract : Flavonoids; Solubility; Phenol red; Citric acid; Chemistry; Natural product chemistry; Organic chemistry; Health sciences; Pharmacology